OPCPP: An Online Plug-Configure-Play Experiment Platform for WSN - Wei Lin; XueHai Hong; Chaonong Xu; YongJun Xu; DengChang Zhao (International Journal of Distributed Sensor Networks)
Wireless sensor network (WSN) experiment platforms are used for teaching, research, and development of WSN. However, existing WSN experiment platforms generally have the following disadvantages: tedious manual operations, invasive measurement method, poor sensor self-awareness, and low resource utilization rate. To address the above problems, this paper proposes OPCPP, an online Plug-Configure-Play experiment platform for WSN. It has four prominent strongpoints: in-application programming in batch, noninvasive measurement method, sensor self-awareness, and remote operation. OPCPP has been used in eight colleges in China for teaching course of “internet of things” till now. We also develop a sensor-aware ZigBee-based smart home system prototype based on OPCPP.